(untitled) (Research, Society and Development, 2022)
Despite plastic packaging being part of human life, much has been said about alternatives to replace the production of those that come from oil. As an exciting strategy, starch, especially cassava starch, stands out as a biodegradable source, which, when compared to the material of fossil origin, has high biodegradability and advantages through use. Many studies have already demonstrated some advantages and limitations of this raw material, however, more information on the subject becomes relevant since Brazil is a major producer of starch and the production of renewable packaging is of global interest. Thus, the objective of this narrative literature review was to address biodegradable packaging as a promising alternative to contain the unbridled advance of non-degradable waste production, demonstrating different applications of edible films and coatings of a biodegradable character based on cassava starch. In this context, several current findings were included in this review to expose the concept of biodegradable packaging, in addition to demonstrating that the biodegradability of packaging can be affected by the characteristics of the polymer used, and in this sense, starch showed a shorter degradation time than others. polymeric materials and advantages for their use in packaging. Thus, this review can serve for a wide range of opportunities to know cassava starch as a biopolymer available to be used on an industrial scale, thus ensuring greater biodegradability of materials from this polymer matrix and consequently less damage to the environment.